2021
DOI: 10.1002/ajh.26338
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin level predicts response to treatment with romiplostim in chemotherapy‐induced thrombocytopenia

Abstract: Chemotherapy-induced thrombocytopenia (CIT) is a common complication of cancer treatment. Evidence has emerged supporting use of romiplostim to treat CIT but predicting clinical response to romiplostim is not possible. To determine utility of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…56,57,60 It was demonstrated that BM infiltration, prior pelvic irradiation, and prior exposure to temozolomide were predictive of non-response to ROMI, while lower TPO levels were correlated with better responses. 58,59 While ROMI was mostly utilized for CIT treatment, EP was mostly tested for CIT prevention, with available data suggesting a potential benefit. [62][63][64] Most recent studies explored avatrombopag's use for CIT management, also pointing at a potential therapeutic use.…”
Section: Thrombopoietin Receptor Agonists In Other Hematologic Malign...mentioning
confidence: 99%
See 4 more Smart Citations
“…56,57,60 It was demonstrated that BM infiltration, prior pelvic irradiation, and prior exposure to temozolomide were predictive of non-response to ROMI, while lower TPO levels were correlated with better responses. 58,59 While ROMI was mostly utilized for CIT treatment, EP was mostly tested for CIT prevention, with available data suggesting a potential benefit. [62][63][64] Most recent studies explored avatrombopag's use for CIT management, also pointing at a potential therapeutic use.…”
Section: Thrombopoietin Receptor Agonists In Other Hematologic Malign...mentioning
confidence: 99%
“…51 Moreover, aforementioned studies proved TPO-RAs' safety and tolerability, whereas thromboembolic event rates were analogous to those historically observed in cancer patients. [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] As seen in ►Table 1, available data from trials have reported different thromboembolic event (TEE) rates, with avatrombopag yielding the lowest TEE rates. [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] It is not certain whether these differences can be solely attributed to the type of TPO-RA that has been used; however, similar results, indicating low rates of thrombosis with avatrombopag, have also been reported in patients with CLD.…”
Section: Thrombopoietin Receptor Agonists In Other Hematologic Malign...mentioning
confidence: 99%
See 3 more Smart Citations